THE ASSOCIATION BETWEEN BODY MASS INDEX AND HANDGRIP STRENGTH AMONG HIV AND AIDS INPATIENTS - Ananda Zahrah Sectio Nugraheny; Farapti Farapti (Universitas Airlangga, 2020)
Background: Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) patients are vulnerable to a decreasing nutritional status. Nutritional status is one of the factors that can affect body mass, which correlates with handgrip strength. Purpose: This study aims to describe the body mass index (BMI) and handgrip strength profiles of HIV and AIDS inpatients. Method: A cross-sectional design was used in this observational study. The population were HIV and AIDS inpatients between August and September 2018. The patients were selected using a purposive sampling technique; 16 patients met the inclusion criteria of the study. Primary data were collected via questionnaire and measuring handgrip strength, while secondary data were collected from the patients’ medical records. A descriptive test was used for the analysis. Results: Most of the HIV and AIDS inpatients were male (81.25%), were between 20 and 39 years old (75.00%), were employed (50.00%), had a middle education level (62.50%), had been hospitalized for four to five days (categorized as a short length of stay; 75.00%), had been diagnosed with HIV for five years or more (87.50%), and were in the third HIV clinical stage (68.75%). The HIV and AIDS inpatients had an average BMI of 19.19±2.48 kg/m2; with 18.75% severely underweight patients, 25% mildly underweight patients, and no overweight patients. The average handgrip strength was 20.58±10.6 kg and 43.75% of patients were classified as having a low handgrip strength. Conclusion: Malnutrition still leads to nutritional problems in HIV and AIDS inpatients.